Local Community Involvement In Ecotourism Activities And Their Perceptions On Collaboration Management In Bhawal National Park, Bangladesh - Sheikh, Altaf Hossain (2007)

(untitled)
This study investigated the local community involvement in collaboration management of Bhawal National Park (BNP), Bangladesh. A survey was conducted from December 2006 to February 2007. A total of 215 respondents comprising the personnel of the National Park management (government staff) and local communities living surrounding park areas including people working in the park as nature tourist guides, in food supply and tourist transportation were surveyed. The main objective of this study was to determine local community involvement in resource protection for ecotourism through a collaborative management arrangement. The survey was administered using structured interview questionnaires to obtain the respondents opinions (perceptions) by using convenience sampling technique. The questionnaire covers the perceptions regarding tourism or specifically ecotourism activities, park management problems, impacts on natural resources, relationship of the local community with the park administration including their level ofparticipation and their willingness to take part in collaborative management of the national park. Various statistical analysis namely Exploratory Data Analysis (EDA), descriptive statistics, Chi-square (χ²) test of Independence, non-parametric test such as Mann-Whitney test and Kruskal-Wallis test, factor analysis and finally regression analysis were used to analyse the data. Principal Component Analysis (PCA) was used to develop index of key variables to be considered in measuring differences in collaborative management factors. The study finds that the ecotourism activities are mainly carried out by the park administration. The main problems faced are shortage of manpower to manage the area, grazing, boundary conflict with the local community, land ownership conflicts with the local community (private lands in the park), illegal settlement and illegally cutting of trees. Tourism impacts such as degradation of ground cover plants, disturbances of wildlife, littering, noise and water pollution are widespread. Results of χ² test showed that the relationship between the local community and park administration is not significant where their participation in the management is minimal. The park usually carried out its management and decisions making process independently and the opinion of the local community is not taken into consideration in such processes. The results of factor analysis showed that the collaborative management factors of Bhawal National Park include joint action management (JAM) (Eigen value: 1.822), shared decision making (SDM) (Eigen value: 1.608) and training and delivery of indigenous knowledge (TDIK) (Eigen value: 1.518). In further analysis, influences of respondents’ demographic background on their perceptions on collaboration management were measured using OLS regression method. The explanatory variables include age, income, education, distance of residence from the national park boundary and main occupation in addition. Results of the regression analysis showed that respondents’ socio-demographic backgrounds such as income, education and occupation have significant relationships with collaborative management variables such as training and sharing of indigenous knowledge (TDIK). The overall findings of the study provide support for the involvement of local community in national park management such as the national parks’ land management, protection of national park resources, ecotourism practices and its overall development.